Introductory notes for the application for a declaration of invalidity of a legal transaction from the civil perspective: Critical analysis of the position of the Fifth Civil Cassation Plenary regarding the challenging of collegiate associative transactions - Campos García, Héctor Augusto (2014)
In August 2014, the Peruvian Supreme Courten acted  the  Fifth  Civil  Cassation Plenary, which establishes that any challenging madeto an associative agreement must be realized through the procedure referred to in the article92 of the Peruvian Civil Code. The comments and criticisms to this decision have not beenfew, considering the complexity of the theme discussed in the aforementioned decision.In this context, with the present article the author realizes a thorough critique of such Cassation Plenary. Based on the analysis of civil and procedural legal concepts, he reaches a conclusion: That the plenary decision, besides of having multiple legal errors, won't accomplish its purpose.